Transformative Librarian: Strategi Transformasi Perpustakaan Bank Indonesia Dalam Mewujudkan Librarian 4.0 - Zaidan Abdurrahman Qois; Rina Tri Utami; Shiddieq Adhityarahman (Jurnal IPI (Ikatan Pustakawan Indonesia), 2023)
Today, transformation is not a new thing; in fact, it has become a necessity for every organization and even individuals in order to survive in conditions full of uncertainty as it is today. Libraries as information institutions are also required to change and transform into libraries 4.0 that are able to maximize the potential of digital technology in building social inclusion to improve people's welfare. Librarians as the life and core of the library must transform into a more advanced direction. Therefore, an effective librarian transformation strategy is necessary as a guide and direction for librarians to achieve their ideal form in the future. Based on that, this study aims to explore and explain in detail the transformative librarian concept, which needed in the process of transforming librarians to librarian 4.0 as an ideal form of future librarians. This research uses a qualitative approach through the literature study method on reference sources in the form of books, scientific articles, and information contained on social media such as YouTube, and direct observation at the Bank Indonesia’s Library. The results present in detail the transformative librarian concept—the values, attitudes, and character of a proactive librarian to become a learner, mentor, servant, and agent of changes for the society or their potential community—which is a key strategy for the successful transformation of librarians into librarian 4.0. In addition, the results of the study also explore knowledge related to librarians and their development, the form of librarian 4.0 as an ideal form of future librarians, understanding of the role and function of librarians, and of course the best practices carried out by the Bank Indonesia’s Library in the transformation and competency development of Bank Indonesia librarians.